Development of Physics E-book Based on Technological Pedagogical Content Knowledge (TPACK) on Thermodynamic Laws Topic - Baihaqi, H K; Purwaningsih, E.; Sulur, S; Sutopo, S (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
This research was developmental research with aims to develop, knowing validity and practicability of thermodynamics e-book based on TPACK. This research was using 4D models and did only as far as develop step. The result based on 4D model steps were (1) Define produces task analysis to fulfil 21st century skill, (2) Design produces 2 product which are teacher book and student book, (3) Develop step produces result of validation and the last product (e-book/flipbook for teacher and student). Expert validation showed the teaching instructional material is valid, learning planning is valid, Content Representation is valid, and e-book is valid. 89,5% students responded this e-book very interesting. This e-book can be said quite practically. Limited trial and small experiment were carried out in one of class in senior high school of one Ngoro Mojokerto and concluded that the increase in the stabilization of sub-topic introduction to Temperature and the Thermodynamics Zero Low is high through the activity of comparing (Let’s Compare). Students can learn thermodynamics by keeping up with science and technology developments by this e-book. The practical benefit is helping the success of learning process carried out at school and home because e-books are provided in 2 forms, teacher book and student book.